Oxford Reading Tree: Level 6: Floppy's Phonics Non-Fiction: The Ragged School level 6 : floppy's phonics non-fiction : the ragged school - Llewellyn, Claire; Hughes, Monica; Page, Thelma; Hunt, Roderick; Brychta, Mr. Alex. (UK Oxford University Press, 2011)
Floppy's Phonics Non-fiction allow children to practise their decoding and literacy skills in the context of exciting non-fiction books, which include a variety of text types and topics, and support from Biff, Chip, Kipper and Floppy. Books contain inside cover notes to support children in their reading. Help with childrens reading development is also available at www.oxfordowl.co.uk. There are 6 Floppy's Phonics Non-fiction titles available at Level 6: Grow a Pumpkin: This book tells you how to grow a pumpkin - and what to do with it when you have grown it! Visit Paris! Is Paris a good place to visit? Read about one family's trip to Paris, and make up your own mind! All About Robin Hood: Was Robin Hood a real person, or was he just a legend? The Ragged School: Find out about school life long ago. look out - the teachers were very strict! Olympic Dreams: Find out about the Olympics - a fantastic festival of sport! Giant Animals: Find out about the world's biggest animals - from giant spiders and moths to elephants and whales!